Penerapan Prinsip Desain Richard Rogers Di Pekanbaru Dalam Perancangan E-Sports Center - Bimantara Asnur; Yohannes Firzal; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The e-Sports center is motivated by the rapid development of e-Sports in Indonesia, including Pekanbaru, various events are held means that e-Sports high enthusiasts today. E-Sports has becomea sport that has formalized and fully supported by the government, as a promising sport for athletes in the future. However, with such rapid development, it is not followed by facilities that couldaccommodate the events, therefore the center of the e-Sports aims to meet all the needs of buildings and other facilities so that e-Sports are even better. In planning the e-Sports Center, it is based onRichard Roger’s design principles about "problem-solving technology" which is how to utilize technology in solving problems and meeting the development needs in architecture. The results ofthis design are the concept of Land of Dawn, legibility, circulation, and zoning in the Land of Dawn by the Rogers principle to accommodate public buildings with a variety of activities in it.Keywords: e-Sports Center, Richard Rogers, Problem-solving